Advances in Affective and Pleasurable Design Proceedings of the AHFE 2017 International Conference on Affective and Pleasurable Design, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book discusses the latest advances in affective and pleasurable design. It reports on important theoretical and practical issues, covering a wealth of topics including aesthetics in product and system design, design-driven innovation, affective computing, evaluation tools for emotion, Kansei engineering for products and services, and many more. This timely survey addresses experts and industry practitioners with different backgrounds, such as industrial designers, emotion designers, ethnographers, human-computer interaction researchers, human factors engineers, interaction designers, mobile product designers, and vehicle system designers. Based on the AHFE 2017 International Conference on Affective and Pleasurable Design, held on July 17-21, 2017, in Los Angeles, California, USA, the book provides an inspiring guide for all researchers and professionals in the field of design.